An analysis of the regulatory region of the IGF1 gene in professional athletes in youth sports teams - Krych-Garsztka, K.; Mizgajska-Wiktor, H.; Gozdzicka-Jozefiak, A. (Human Movement, 2011)
The aim of this study was to search for single nucleotide changes in the P1 promoter sequence of the IGF1 gene in both high-class athletes and subjects who do not participate in professional sports. The second rationale was to compare the polymorphism frequency in the promoter region in athletes across a variety of sport disciplines. Methods. 272 athletes from the regional sports team of Wielkopolska (Poland) took part in the study. 154 athletes practiced team sports whereas 118 trained in strength sports. The control group comprised of 122 individuals who did not practice sport professionally. Genetic material came from epithelium swabs from the oral cavity, which was then subject to DNA isolation and tested with the PCR/SSCP technique. DNA samples showing different migration in electrophoresis were then sequenced. Results. The frequency of the polymorphisms was substantially higher (p < 0.05) in the athlete group (9.2%) than in the control group (2.4%). A considerably higher frequency of the sequence changes (p < 0.05%) was observed in those athletes who participated in strength sports (11.0%) than in team sports (7.8%). Among all the individuals tested, the -147bp -475bp region was the most polymorphic, yet changes within this fragment were not detected in the control group. In the control group the most often change in the nucleotide sequence was observed at position -1089 (T/C), while in the athlete group at position -383 (C/T). Change at position -1089 (T/C), found in eight individuals, is related to a potential binding site of the AP-1 transcription factor. Change at position -361 (G/A), detected in two individuals, is probably the site for the Sp1 transcription factor. Conclusion. The conducted study found that single nucleotide polymorphism of the P1 promoter region of the IGF1 gene is more frequent in athletes than in non-athletes. We believe that the variation in the P1 promoter sequence of this gene is related to an organism's adaptation to physical (especially strength) activity.